2014 American Control Conference 2014
DOI: 10.1109/acc.2014.6859201
|View full text |Cite
|
Sign up to set email alerts
|

Finite-time consensus on the median value by discontinuous control

Abstract: In this paper we propose a novel protocol to solve the consensus on the median value problem, i.e., the decentralized agreement problem for networked multi-agent systems where the quantity of interest is the median value as opposed to the average value of the agents' states. The median value is a statistical measure particularly robust to the existence of outlier agents which are a significant issue in large scale averaging networks. The proposed protocol achieves consensus on the median value in finite time b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In [33] the authors introduced a distributed protocol for a second order multi-agent system able to reach consensus in finite-time under the presence of bounded disturbances while also maintaining the initial topology. A finite-time consensus on the median value is analyzed in [36], [39] where the authors showed that the proposed protocol is also robust to uncooperative agents if the network possesses a topological property known as k-safety.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…In [33] the authors introduced a distributed protocol for a second order multi-agent system able to reach consensus in finite-time under the presence of bounded disturbances while also maintaining the initial topology. A finite-time consensus on the median value is analyzed in [36], [39] where the authors showed that the proposed protocol is also robust to uncooperative agents if the network possesses a topological property known as k-safety.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…To reduce complexity, in Tumova & Dimarogonas, 2015, summaries of independent movements of individual agents are made; and, in Schillinger et al, 2016, a way to identify independent parts of a given mission is proposed as a finite LTL formula. Some works have proposed algorithmic solutions for movement planning problems in various scenarios, such as synthesis of high-level tasks (Guo & Dimarogonas, 2015a,Kloetzer & Mahulea, 2015, consensus problems (Aragues et al, 2012,Franceschelli et al, 2014, and leading follower (Garrido et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is relatively little work that treats finite-time consensus in the presence of adversarial agents. Some examples include the excellent results in [17], [18]. However, in [17] it is assumed that only the initial conditions of certain agents are faulty, with all agents applying the nominally specified control protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples include the excellent results in [17], [18]. However, in [17] it is assumed that only the initial conditions of certain agents are faulty, with all agents applying the nominally specified control protocol. In contrast, Byzantine adversaries may apply an arbitrary control protocol at any instant subsequent to the initial time.…”
Section: Introductionmentioning
confidence: 99%